The Stone Fireplaces of Denendeh - Carroll, Patrick (Material Culture Review / Revue de la culture matérielle, 2024)
Stone fireplaces and chimneys have been documented in nineteenth century Indigenous settlement sites in the Northwest Territories. The cabin and chimney designs were adapted by Dene craftsmen based on examples they encountered when engaging with Euro-Canadian traders and explorers. The Indigenous cabins and chimneys were built during a period of transition in Dene culture, at a time when they began the process of integrating into a fur trade economy. The chimneys and cabins are elements of Euro-Canadian vernacular architecture adapted by Indigenous people in the north. The Indigenous cabins and chimneys are an example of cultural diffusion and, in some instances, might have also been expressions of social status. Together, the Indigenous stone chimneys and the extant chimney features at Fort Confidence and Fort Reliance in the Northwest Territories are part of a shared architectural heritage.